Fast-curing EVA hot melt adhesive and preparation process thereof
By introducing island-shaped coated carbonized bagasse fibers into EVA hot melt adhesive, the problem of decreased bonding performance of EVA hot melt adhesive when the curing speed is increased is solved, achieving both rapid curing and high bonding performance.
Patent Information
- Application Number
- CN202411391484.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-10-08
AI Technical Summary
While improving the curing speed, it is difficult to take into account its good bonding properties.
By introducing self-made island-coated carbonized bagasse fibers as fillers into the EVA resin system and limiting the preparation process, the crystallization rate after the EVA resin molecules are melted is increased and the cohesion is enhanced.
The EVA hot melt adhesive has both good bonding performance and rapid curing ability, improving the overall performance of the product.
Smart Images

Figure BDA0005072547390000091 
Figure BDA0005072547390000101
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of polymer adhesives and more specifically relates to a fast-curing EVA hot melt adhesive and a preparation process thereof. Background Art
[0002] EVA hot melt adhesive is a thermoplastic adhesive with ethylene-vinyl acetate copolymer (EVA) as the main component. It is solid at room temperature and melts into liquid after being heated to a certain temperature. It has good fluidity and viscosity and is used to bond various materials. EVA hot melt adhesive has the following characteristics:
[0003] High bond strength: EVA hot melt adhesive can provide strong adhesion and is suitable for a variety of substrates such as paper, plastic, metal and wood.
[0004] High initial bond: It has good initial bond and bonds quickly without additional curing or drying process.
[0005] Temperature resistance: EVA hot melt adhesive is resistant to high temperatures and can maintain its bonding properties at higher temperatures. The temperature resistance range is usually between -30°C and 80°C.
[0006] Weather resistance: It is not easily affected by moisture, aging or decomposition, making it suitable for outdoor applications and long-term use.
[0007] Environmental protection: EVA hot melt adhesive is solvent-free, non-toxic, has no pollution to the environment, and meets environmental protection requirements.
[0008] Good flexibility: EVA hot melt adhesive has good flexibility, is not easy to break and become brittle, and is suitable for applications that require bending or bearing pressure.
[0009] In order to increase the curing speed of EVA resin, generally speaking, the VA (vinyl acetate) content in EVA resin is reduced; or a tackifier with a high softening point is added; or wax is added. However, the above methods will lead to a decrease in the bonding performance of EVA hot melt adhesive. Therefore, how to increase its curing speed while ensuring its good bonding performance is one of the technical problems that technicians in this field still need to face. Summary of the invention
[0010] The technical problem to be solved by the present invention is that in the commonly used EVA hot melt adhesive system, in order to obtain a faster curing rate, it is often difficult to take into account its better bonding performance. The present invention provides a fast-curing EVA hot melt adhesive and a preparation process thereof.
[0011] The invention aims to provide a fast-curing EVA hot-melt adhesive.
[0012] Another object of the present invention is to provide a preparation process of a fast-curing EVA hot-melt adhesive.
[0013] The above-mentioned purpose of the present invention is achieved through the following technical solutions:
[0014] A fast-curing EVA hot-melt adhesive comprises the following raw materials in parts by weight:
[0015] 150-160 parts of EVA resin, 100-110 parts of tackifying resin, 30-40 parts of wax, 10-12 parts of antioxidant and 30-35 parts of filler;
[0016] The filler includes island-shaped coated carbonized bagasse fibers;
[0017] The steps for preparing the island-shaped coated carbonized bagasse fiber include:
[0018] Disperse bagasse fiber in an ethanol solution, adjust the pH to 7.5-8.0, then drop a silane coupling agent under stirring, heat and stir to react, then drop ethyl orthosilicate, after the addition is complete, continue heating and stirring to react, after the reaction is complete, filter, wash and dry to obtain a precursor;
[0019] The obtained precursor is heated to 380-400°C at a rate of 6-8°C / min, and then heated to 880-900°C at a rate of 0.9-1.5°C / min, carbonized at the temperature, cooled, and discharged to obtain island-shaped coated carbonized bagasse fibers.
[0020] The above scheme introduces homemade island-shaped coated carbonized bagasse fiber as filler in the EVA resin system, and defines the preparation process of the corresponding island-shaped coated carbonized bagasse fiber. In the above preparation process, first, under alkaline conditions, the silane coupling agent is hydrolyzed, thereby adsorbed on the surface of the bagasse fiber, and then on this basis, ethyl orthosilicate is further added to hydrolyze it. The hydrolysis product is adsorbed and fixed on the surface of the bagasse fiber under the action of the silane coupling agent, and then the bagasse fiber is carbonized by heating. In this process, it is first dehydrated by a rapid heating rate, and then the heating rate is significantly slowed down. During the slow heating process, the ethyl orthosilicate hydrolysis product is coated on the bagasse fiber. The surface of the bagasse fiber can rely on it to have a certain supporting effect. Therefore, due to the inconsistent stress in different parts, the bagasse fiber will be twisted to a certain extent. As a result, the carbonized bagasse fiber can obtain ideal mechanical strength and be dispersed in a twisted state. This will facilitate the physical entanglement between the molecular chains of the bagasse fiber and the EVA resin, thereby enhancing the bonding strength between the two and improving the cohesive force, thereby ensuring the bonding performance of the product. At the same time, it improves the crystallization rate of the EVA resin molecules after melting, and accelerates the curing process of the product. Therefore, the product can have good bonding performance and rapid curing ability.
[0021] Furthermore, the aspect ratio of the bagasse fiber is (20-25):1, and the diameter of the bagasse fiber is 8-12 μm.
[0022] The inventors further discovered that by selecting bagasse fibers with a relatively larger aspect ratio, they tend to form more slender carbonized products during the heating carbonization process. In this way, multiple EVA molecular chains are easily entangled on the surface of the same carbonized bagasse fiber, thereby forming a continuous interaction force; more importantly, the slender bagasse fibers are prone to form a three-dimensional twisted spiral structure when the structure is distorted under the action of thermal stress, thereby avoiding relative slippage between the carbonized bagasse fibers and the EVA molecular chains when subjected to external forces, thereby further enhancing the bonding strength of the product.
[0023] Furthermore, the silane coupling agent is selected from any one of silane coupling agent KH-550, silane coupling agent KH-560 and silane coupling agent KH-570.
[0024] Furthermore, the amount of the silane coupling agent used is 3-5% of the mass of the bagasse fiber; and the amount of the tetraethyl orthosilicate used is 6-8% of the mass of the bagasse fiber.
[0025] By adjusting the dosage of the above two raw materials, it is mainly considered that a small amount of silane coupling agent is used, so that it is only locally adsorbed on the surface of bagasse fiber. Therefore, the amount of ethyl orthosilicate is also relatively small. Under this ratio, a corresponding island distribution can be formed, thereby constructing a greater difference in stress between different parts, which promotes the formation of a twisted state of the product during the heating and carbonization process.
[0026] Furthermore, in the EVA resin, the mass content of VA is 28-32%; and the melt index of the EVA resin is 100-150.
[0027] Furthermore, the tackifying resin is selected from any one of rosin glycerol ester, hydrogenated rosin resin, α-terpene resin, lemon terpene resin, C5 petroleum resin, and C5 hydrogenated petroleum resin.
[0028] Furthermore, the wax is selected from any one of Fischer-Tropsch wax, polyethylene wax, microcrystalline wax, and paraffin wax.
[0029] Furthermore, the antioxidant is selected from any one of antioxidant 264 and antioxidant 1010.
[0030] A preparation process of a fast-curing EVA hot melt adhesive, the specific preparation steps comprising:
[0031] Weigh each component according to the raw material composition;
[0032] At a temperature of 170-175°C, first mix the tackifying resin and filler, mix them evenly at a low speed, then add the wax, antioxidant and EVA resin, continue heating and stirring quickly to mix evenly, and discharge the material to obtain a fast-curing EVA hot melt adhesive.
[0033] Furthermore, the low-speed shear mixing includes: continuous shear mixing for 30-45 minutes at a shear rate of 160-180 r / min; and the heating rapid stirring mixing includes: rapid stirring mixing for 20-30 minutes at a stirring speed of 800-900 r / min.
[0034] By first adopting a lower shear rate, the tackifying resin is melted and then mixed with the filler. In this process, since the tackifying resin still maintains a relatively high viscosity after being melted, the physical structure of the carbonized bagasse fiber of the filler can be fully stretched in the low-speed shear process, combined with the effect of physical shear force, and the problem of excessive accumulation of molecular chains after twisting of the slender bagasse fibers, especially, is avoided, making it difficult to disperse them in the system. DETAILED DESCRIPTION
[0035] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0036] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0037] Example 1
[0038] Preparation of island-coated carbonized bagasse fibers:
[0039] After bagasse fiber and 30% ethanol solution by mass fraction were mixed in a mass ratio of 1:8, the pH was adjusted to 7.5, and then the silane coupling agent was added dropwise at a rate of 8 mL / min while stirring at a temperature of 40°C and a stirring speed of 300 r / min. After the addition of the silane coupling agent was completed, heating and stirring were continued for 30 minutes, and then tetraethyl orthosilicate was added dropwise at a rate of 8 mL / min under stirring. After the addition of tetraethyl orthosilicate was completed, heating and stirring were continued for 40 minutes. After the reaction was completed, the filter cake was filtered and collected, and the filter cake was washed twice with deionized water, and then the washed filter cake was transferred to an oven for drying, and dried to a constant weight at a temperature of 100°C to obtain a precursor;
[0040] Wherein, the aspect ratio of the bagasse fiber is 20:1, and the diameter of the bagasse fiber is 8 μm;
[0041] The silane coupling agent is selected from silane coupling agent KH-550;
[0042] The amount of the silane coupling agent is 3% of the mass of the bagasse fiber; and the amount of the tetraethyl orthosilicate is 6% of the mass of the bagasse fiber;
[0043] The obtained precursor was transferred into a carbonization furnace, and was heated to 380°C at a rate of 6°C / min under an argon atmosphere, and then heat-treated for 1 hour, and then heated to 880°C at a rate of 0.9°C / min, and carbonized for 2 hours, and then cooled to room temperature with the furnace, and discharged to obtain island-shaped coated carbonized bagasse fibers, which were fillers;
[0044] Preparation of hot melt adhesive:
[0045] According to weight, 150 parts of EVA resin, 100 parts of tackifying resin, 30 parts of wax, 10 parts of antioxidant and 30 parts of island-shaped coated carbonized bagasse fiber are taken in sequence;
[0046] The mass content of VA in the EVA resin is 28%; and the melt index of the EVA resin is 100;
[0047] The tackifying resin is selected from rosin glycerol ester;
[0048] The wax is selected from Fischer-Tropsch wax;
[0049] The antioxidant is selected from antioxidant 264;
[0050] At a temperature of 170°C, the tackifying resin and filler are first mixed, and then pressed at a shear rate of 160r / min, and the shear mixing is continued for 30 minutes. Subsequently, wax, antioxidant and EVA resin are added, and the stirring speed is continued at 800r / min. Rapid stirring and mixing for 20 minutes, the material is discharged, and cooled to obtain a fast-curing EVA hot melt adhesive.
[0051] Example 2
[0052] Preparation of island-coated carbonized bagasse fibers:
[0053] Bagasse fiber and 35% ethanol solution were mixed in a mass ratio of 1:9, and the pH was adjusted to 7.8. Then, at a temperature of 40°C and a stirring speed of 350 r / min, a silane coupling agent was added dropwise at a rate of 9 mL / min while stirring. After the addition of the silane coupling agent was completed, heating and stirring were continued for 35 minutes. Then, tetraethyl orthosilicate was added dropwise at a rate of 9 mL / min under stirring. After the addition of tetraethyl orthosilicate was completed, heating and stirring were continued for 50 minutes. After the reaction was completed, the filter cake was filtered and collected, and the filter cake was washed with deionized water for 3 times. The washed filter cake was then transferred to an oven for drying, and dried to a constant weight at a temperature of 100°C to obtain a precursor.
[0054] Wherein, the aspect ratio of the bagasse fiber is 22:1, and the diameter of the bagasse fiber is 10 μm;
[0055] The silane coupling agent is selected from silane coupling agent KH-560;
[0056] The amount of the silane coupling agent is 4% of the mass of the bagasse fiber; and the amount of the ethyl orthosilicate is 7% of the mass of the bagasse fiber;
[0057] The obtained precursor was transferred into a carbonization furnace, and was heated to 390°C at a rate of 7°C / min under an argon atmosphere, and then heat-treated for 1.5 hours, and then heated to 890°C at a rate of 1.2°C / min, and carbonized for 3 hours, and then cooled to room temperature with the furnace, and discharged to obtain island-shaped coated carbonized bagasse fibers, which were fillers;
[0058] Preparation of hot melt adhesive:
[0059] In parts by weight, 155 parts of EVA resin, 105 parts of tackifying resin, 35 parts of wax, 11 parts of antioxidant and 32 parts of island-shaped coated carbonized bagasse fiber are taken in sequence;
[0060] The mass content of VA in the EVA resin is 30%; and the melt index of the EVA resin is 120;
[0061] The tackifying resin is selected from α-terpene resin;
[0062] The wax is selected from polyethylene wax;
[0063] The antioxidant is selected from antioxidant 1010;
[0064] At a temperature of 172°C, the tackifying resin and filler are first mixed, and then pressed at a shear rate of 170r / min, and the shear mixing is continued for 35 minutes. Subsequently, wax, antioxidant and EVA resin are added, and the stirring speed is continued at 850r / min. Rapid stirring and mixing for 25 minutes, the material is discharged, and cooled to obtain a fast-curing EVA hot melt adhesive.
[0065] Example 3
[0066] Preparation of island-coated carbonized bagasse fibers:
[0067] Bagasse fiber and 40% ethanol solution by mass fraction were mixed in a mass ratio of 1:10, and the pH was adjusted to 8.0. Then, a silane coupling agent was added dropwise at a rate of 10 mL / min while stirring at a temperature of 40°C and a stirring speed of 400 r / min. After the addition of the silane coupling agent was completed, heating and stirring were continued for 45 minutes. Then, tetraethyl orthosilicate was added dropwise at a rate of 10 mL / min under stirring. After the addition of tetraethyl orthosilicate was completed, heating and stirring were continued for 60 minutes. After the reaction was completed, the filter cake was filtered and collected, and the filter cake was washed with deionized water for 4 times. The washed filter cake was then transferred to an oven for drying, and dried to a constant weight at a temperature of 100°C to obtain a precursor.
[0068] Wherein, the aspect ratio of the bagasse fiber is 25:1, and the diameter of the bagasse fiber is 12 μm;
[0069] The silane coupling agent is selected from silane coupling agent KH-570;
[0070] The amount of the silane coupling agent is 5% of the mass of the bagasse fiber; and the amount of the tetraethyl orthosilicate is 8% of the mass of the bagasse fiber;
[0071] The obtained precursor was transferred into a carbonization furnace, and was heated to 400°C at a rate of 8°C / min under an argon atmosphere, and then heat-treated for 2 hours, and then heated to 900°C at a rate of 1.5°C / min, and carbonized for 4 hours, and then cooled to room temperature with the furnace, and discharged to obtain island-shaped coated carbonized bagasse fibers, which were fillers;
[0072] Preparation of hot melt adhesive:
[0073] In parts by weight, 160 parts of EVA resin, 110 parts of tackifying resin, 40 parts of wax, 12 parts of antioxidant and 35 parts of island-shaped coated carbonized bagasse fiber are taken in sequence;
[0074] The mass content of VA in the EVA resin is 32%; and the melt index of the EVA resin is 150;
[0075] The tackifying resin is selected from C5 hydrogenated petroleum resin;
[0076] The wax is selected from microcrystalline wax;
[0077] The antioxidant is selected from antioxidant 264;
[0078] At a temperature of 175°C, the tackifying resin and filler are first mixed, and then pressed at a shear rate of 180 r / min, and the shear mixing is continued for 45 minutes. Subsequently, wax, antioxidant and EVA resin are added, and the stirring speed is continued at 900 r / min. Rapid stirring and mixing for 30 minutes, the material is discharged, and cooled to obtain a fast-curing EVA hot melt adhesive.
[0079] Example 4
[0080] The present embodiment is different from the embodiment 1 in that the amount of the silane coupling agent used is 8% of the mass of the bagasse fiber; and the amount of the tetraethyl orthosilicate used is 12% of the mass of the bagasse fiber, and the other conditions remain unchanged.
[0081] Example 5
[0082] The present embodiment is different from the embodiment 1 in that the aspect ratio of the bagasse fiber is 12:1, and the diameter of the bagasse fiber is 8 μm; the other conditions remain unchanged.
[0083] Example 6
[0084] Compared with Example 1, this embodiment is different in that:
[0085] Preparation of hot melt adhesive:
[0086] According to weight, 150 parts of EVA resin, 100 parts of tackifying resin, 30 parts of wax, 10 parts of antioxidant and 30 parts of island-shaped coated carbonized bagasse fiber are taken in sequence;
[0087] The mass content of VA in the EVA resin is 28%; and the melt index of the EVA resin is 100;
[0088] The tackifying resin is selected from rosin glycerol ester;
[0089] The wax is selected from Fischer-Tropsch wax;
[0090] The antioxidant is selected from antioxidant 264;
[0091] At a temperature of 170° C., the tackifying resin, filler, wax, antioxidant and EVA resin are rapidly stirred and mixed at a stirring speed of 800 r / min for 50 minutes, discharged, and cooled to obtain a fast-curing EVA hot melt adhesive;
[0092] The rest of the conditions remain unchanged.
[0093] Comparative Example 1
[0094] Compared with Example 1, this comparative example has the following differences:
[0095] Preparation of island-coated carbonized bagasse fibers:
[0096] Bagasse fiber and 30% ethanol solution by mass fraction were mixed in a mass ratio of 1:8, and the pH was adjusted to 7.5. Then, a silane coupling agent was added dropwise at a rate of 8 mL / min while stirring at a temperature of 40°C and a stirring speed of 300 r / min. After the addition of the silane coupling agent was completed, the mixture was heated and stirred for reaction for 30 minutes. After the reaction was completed, the filter cake was filtered and collected, and the filter cake was washed twice with deionized water. The washed filter cake was then transferred to an oven for drying, and dried to a constant weight at a temperature of 100°C to obtain a precursor.
[0097] Wherein, the aspect ratio of the bagasse fiber is 20:1, and the diameter of the bagasse fiber is 8 μm;
[0098] The silane coupling agent is selected from silane coupling agent KH-550;
[0099] The amount of the silane coupling agent is 3% of the mass of the bagasse fiber; and the amount of the tetraethyl orthosilicate is 6% of the mass of the bagasse fiber;
[0100] The obtained precursor was transferred into a carbonization furnace, and was heated to 380°C at a rate of 6°C / min under an argon atmosphere, and then heat-treated for 1 hour, and then heated to 880°C at a rate of 0.9°C / min, and carbonized for 2 hours, and then cooled to room temperature with the furnace, and discharged to obtain island-shaped coated carbonized bagasse fibers, which were fillers;
[0101] The rest of the conditions remain unchanged.
[0102] Comparative Example 2
[0103] Compared with Example 1, this comparative example has the following differences:
[0104] Preparation of island-coated carbonized bagasse fibers:
[0105] After bagasse fiber and 30% ethanol solution by mass fraction were mixed in a mass ratio of 1:8, the pH was adjusted to 7.5, and then the silane coupling agent was added dropwise at a rate of 8 mL / min while stirring at a temperature of 40°C and a stirring speed of 300 r / min. After the addition of the silane coupling agent was completed, heating and stirring were continued for 30 minutes, and then tetraethyl orthosilicate was added dropwise at a rate of 8 mL / min under stirring. After the addition of tetraethyl orthosilicate was completed, heating and stirring were continued for 40 minutes. After the reaction was completed, the filter cake was filtered and collected, and the filter cake was washed twice with deionized water, and then the washed filter cake was transferred to an oven for drying, and dried to a constant weight at a temperature of 100°C to obtain a precursor;
[0106] Wherein, the aspect ratio of the bagasse fiber is 20:1, and the diameter of the bagasse fiber is 8 μm;
[0107] The silane coupling agent is selected from silane coupling agent KH-550;
[0108] The amount of the silane coupling agent is 3% of the mass of the bagasse fiber; and the amount of the tetraethyl orthosilicate is 6% of the mass of the bagasse fiber;
[0109] The obtained precursor was transferred into a carbonization furnace, and heated to 880°C at a rate of 6°C / min under an argon atmosphere, and carbonized for 2 hours at that temperature, and then cooled to room temperature with the furnace, and the material was discharged to obtain island-shaped coated carbonized bagasse fibers, which were fillers;
[0110] The rest of the conditions remain unchanged.
[0111] The products obtained from the above embodiments and comparative examples were subjected to relevant performance tests, and the specific test methods and test results are as follows:
[0112] Soak and polish a 100mm×50mm×1mm stainless steel sheet in ethanol, dry it, and set it aside. Next, use the EVA hot melt adhesive prepared in the above embodiment or comparative example to bond the two steel sheets together, where the size of the middle bonding area is 20mm×20mm, and the glue coating thickness is 0.6mm. When applying the glue, ensure that the thickness of the glue layer is uniform. After the specimen is bonded, place it on a closed electric furnace at 80°C and press it with a 500g weight for about 30 minutes. Then, use a knife to clean up the glue overflowing around the bonding area. After cooling for 10 minutes, according to the test requirements of the performance indicators, use a ZQS6-2000A bonding strength tester to test the shear strength of the specimen according to GB / T 7124-2008 standard, and obtain a shear strength of 1;
[0113] After soaking and polishing a 100mm×50mm×1mm stainless steel sheet in ethanol, it was dried and treated for use. Next, the two steel sheets were bonded together using the EVA hot melt adhesive prepared in the above embodiment or comparative example, wherein the size of the middle bonding area is 20mm×20mm, and the thickness of the glue coating is 0.6mm. When applying the glue, it is necessary to ensure that the thickness of the glue layer is uniform. After the specimen is bonded, it is placed on a closed electric furnace at 80°C and pressed with a 500g weight for about 15 minutes. Then, a knife is used to clean up the glue overflowing around the bonding area. After cooling for 5 minutes, according to the test requirements of the performance indicators, a ZQS6-2000A bonding strength tester is used to test the shear strength of the specimen according to the GB / T 7124-2008 standard, and a shear strength of 2 is obtained.
[0114] The detailed test results are shown in Table 1;
[0115] Table 1: Product shear strength test results
[0116]
[0117]
[0118] It can be seen from the test results in Table 1 that the product obtained by the present invention has excellent shear strength, and even in a relatively short curing time, it can still obtain excellent bonding performance, which can effectively take into account the bonding performance and rapid curing ability of the product.
[0119] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A fast curing EVA hot melt adhesive, characterized in that: The invention comprises the following raw materials in parts by weight: 150-160 parts of EVA resin, 100-110 parts of tackifying resin, 30-40 parts of wax, 10-12 parts of antioxidant and 30-35 parts of filler; The filler includes island-shaped coated carbonized bagasse fibers; The steps for preparing the island-shaped coated carbonized bagasse fiber include: Disperse bagasse fiber in an ethanol solution, adjust the pH to 7.5-8.0, then drop a silane coupling agent under stirring, heat and stir to react, then drop ethyl orthosilicate, after the addition is complete, continue heating and stirring to react, after the reaction is complete, filter, wash and dry to obtain a precursor; The obtained precursor is heated to 380-400°C at a rate of 6-8°C / min, and then heated to 880-900°C at a rate of 0.9-1.5°C / min, carbonized at the temperature, cooled, and discharged to obtain island-shaped coated carbonized bagasse fibers.
2. A fast curing EVA hot melt adhesive according to claim 1, characterized in that: The aspect ratio of the bagasse fiber is (20-25):1, and the diameter of the bagasse fiber is 8-12 μm.
3. A fast curing EVA hot melt adhesive according to claim 1, characterized in that: The silane coupling agent is selected from any one of silane coupling agent KH-550, silane coupling agent KH-560 and silane coupling agent KH-570.
4. A fast curing EVA hot melt adhesive according to claim 1, characterized in that: The amount of the silane coupling agent used is 3-5% of the mass of the bagasse fiber; and the amount of the tetraethyl orthosilicate used is 6-8% of the mass of the bagasse fiber.
5. The fast curing EVA hot melt adhesive according to claim 1, characterized in that: In the EVA resin, the mass content of VA is 28-32%; and the melt index of the EVA resin is 100-150.
6. A fast curing EVA hot melt adhesive according to claim 1, characterized in that: The tackifying resin is selected from any one of rosin glycerol ester, hydrogenated rosin resin, α-terpene resin, lemon terpene resin, C5 petroleum resin, and C5 hydrogenated petroleum resin.
7. The fast curing EVA hot melt adhesive according to claim 1, characterized in that: The wax is selected from any one of Fischer-Tropsch wax, polyethylene wax, microcrystalline wax and paraffin wax.
8. The fast curing EVA hot melt adhesive according to claim 1, characterized in that: The antioxidant is selected from any one of antioxidant 264 and antioxidant 1010.
9. A process for preparing the fast curing EVA hot melt adhesive according to any one of claims 1 to 8, characterized in that: The specific preparation steps include: Weigh each component according to the raw material composition; At a temperature of 170-175°C, first mix the tackifying resin and filler, mix them evenly at a low speed, then add the wax, antioxidant and EVA resin, continue heating and stirring quickly to mix evenly, and discharge the material to obtain a fast-curing EVA hot melt adhesive.
10. A process for preparing a fast-curing EVA hot melt adhesive according to claim 9, characterized in that: The low-speed shear mixing includes: continuously shearing and mixing for 30-45 minutes at a shear rate of 160-180 r / min; and the heating rapid stirring mixing includes: rapidly stirring and mixing for 20-30 minutes at a stirring speed of 800-900 r / min.
Citation Information
Patent Citations
Polypropylene wood plastic composite plate and preparation method thereof
CN107286464A
EVA hot melt adhesive for rapid box sealing, and preparation method thereof
CN111019559A
Thermal shock resistant fiber reinforced aerogel thermal insulation material and preparation method thereof
CN114538942A
Wax and ethylene vinyl ester copolymer blends
GB1377206A